BRD7 facilitates ferroptosis via modulating clusterin promoter hypermethylation and suppressing AMPK signaling in diabetes-induced testicular damage - Yuehai Xiao; Zongjian Liang; Jun Qiao; Zhiqiang Zhu; Bei Liu; Yuan Tian (BMC, 2024)
Abstract Background Diabetes mellitus (DM)-induced testicular damage is associated with sexual dysfunction and male infertility in DM patients. However, the pathogenesis of DM-induced testicular damage remains largely undefined. Methods A streptozotocin (STZ)-induced diabetic model and high glucose (HG)-treated in vitro diabetic model were established. The histological changes of testes were assessed by H&E staining. Serum testosterone, iron, MDA and GSH levels were detected using commercial kits. Cell viability and lipid peroxidation was monitored by MTT assay and BODIPY 581/591 C11 staining, respectively. qRT-PCR, immunohistochemistry (IHC) or Western blotting were employed to detect the levels of BRD7, Clusterin, EZH2 and AMPK signaling molecules. The associations among BRD7, EZH2 and DNMT3a were detected by co-IP, and the transcriptional regulation of Clusterin was monitored by methylation-specific PCR (MSP) and ChIP assay. Results Ferroptosis was associated with DM-induced testicular damage in STZ mice and HG-treated GC-1spg cells, and this was accompanied with the upregulation of BRD7. Knockdown of BRD7 suppressed HG-induced ferroptosis, as well as HG-induced Clusterin promoter methylation and HG-inactivated AMPK signaling in GC-1spg cells. Mechanistical studies revealed that BRD7 directly bound to EZH2 and regulated Clusterin promoter methylation via recruiting DNMT3a. Knockdown of Clusterin or inactivation of AMPK signaling reverses BRD7 silencing-suppressed ferroptosis in GC-1spg cells. In vivo findings showed that lack of BRD7 protected against diabetes-induced testicular damage and ferroptosis via increasing Clusterin expression and activating AMPK signaling. Conclusion BRD7 suppressed Clusterin expression via modulating Clusterin promoter hypermethylation in an EZH2 dependent manner, thereby suppressing AMPK signaling to facilitate ferroptosis and induce diabetes-associated testicular damage.